Implementation of a Water Nutrient Monitoring System for Integrated IoT-Based Hydroponics at CV Tirta Fertindo - Purnomo, Ananda Pandu Candra; Assariy, Annas Faiz; Prastiawan, Galih; Arifin, Zaenal (LPPM Universitas Dian Nuswantoro, 2025)
CV Tirta Fertindo Pratama is an agribusiness company specializing in hydroponics in Semarang. The company manages hydroponic farms for various vegetables and fruits but faces challenges in manually measuring Potential of Hydrogen (pH), electrical conductivity (EC), and Total Dissolved Solids (TDS), which affect product quality. To address this issue, an Internet of Things (IoT)-based hydroponic plant monitoring system was developed using temperature, pH, and TDS sensors connected to an ESP32 microcontroller. This system enables remote automated measurement and control, displaying data via an LCD. The implementation of this IoT system enhances efficiency and consistency in plant management by enabling real-time monitoring and more precise control, reducing the risk of manual errors, and improving hydroponic crop production. Keywords - hydroponics; IoT; pH; EC; TDS; microcontroller